The Effectiveness Projec Based Learning Methods in Teaching Structure of Indonesian Morpheme - Amrulloh, Roni; Taufiq, Muh (Universitas Hamzanwadi, 2019)
This research was aimed to know the result of learning process by project based learning in the matter of Indonesian language form and structure of its morpheme. This research was a classroom action research with the stages constructing action plan, implementing, monitoring, and reflecting towards the execution process of the action, which was implemented in two cycles. The subjects of the research were 31 students of study program of Indonesian language. While, the data collection methods were observation and test, afterwards the data were processed by descriptive statistic. Base on the analysis result, it was found that average students learning activities in first cycle are 2.71, belonging to the active categories. While, it was found that the percentage of students learning mastery in the cycle 1 was 35.48%. In cycle II the average students learning activities was 77.42%. Due to the students learning mastery in cycle II was higher than 75%, and the students learning activities belonging to the active categories, therefore the mastery in cycle II was achieved.Keywords: project based learning; form; and structure of its morpheme.